Nanostructured Mesoporous Titanium Dioxide Thin Film Prepared by Sol-Gel Method for Dye-Sensitized Solar Cell - Yu-Chang Liu; Yun-Fang Lu; Yz-Zhen Zeng; Chi-Hung Liao; Jen-Chieh Chung; Tsong-Yang Wei (International Journal of Photoenergy)
Titanium dioxide (TiO2) paste was prepared by sol-gel and hydrothermal method with various precursors. Nanostructured mesoporous TiO2 thin-film back electrode was fabricated from the nanoparticle colloidal paste, and its performance was compared with that made of commercial P25 TiO2. The best performance was demonstrated by the DSSC having a 16 μm-thick TTIP-TiO2 back electrode, which gave a solar energy conversion efficiency of 6.03%. The ability of stong adhesion on ITO conducting glass substrate and the high surface area are considered important characteristics of TiO2 thin film. The results show that a thin film with good adhesion can be made from the prepared colloidal paste as a result of alleviating the possibility of electron transfer loss. One can control the colloidal particle size from sol-gel method. Therefore, by optimizing the preparation conditions, TiO2 paste with nanoparticle and narrow diameter distribution was obtained.